Etnomatematika: Eksplorasi Uma Lengge Untuk Pembelajaran Matematika Di Sekolah - Muhamad Farhan; M. Tohimin Apriyanto; Arif Rahman Hakim (Pendidikan Matematika Universitas PGRI Yogyakarta, 2021)
This research was conducted to explore the elements of mathematics (ethnomathematics) contained in the Uma Lengge building that is located in Bima, West Nusa Teggara (NTB), Indonesia. The research used a qualitative method with an ethnographic approach. The data were obtained from literature studies, observation, and documentation. Observation and documentation were used to identify and explore the elements of mathematics (ethnomathematics) contained in the Uma Lengge building, literature studies are used to find out more about the cultural values that exist in the uma lengge building as an application in learning mathematics. The results show elements of mathematics (ethnomathematics) in the uma lengge contain plane figure namely the concept of square, rectangle and triangle, concept of parallel and perpendicular lines, concept of geometry namely triangular prism and concept of similarity in triangle. The implication of this research is that the cultural elements contained in the uma lengge building can be used in mathematics learning applications in schools. Keywords: ethnomathematics, uma lengge, math learning